- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,601

\(\displaystyle (a+b)(b+c)=-1\\(a-b)^2+(a^2-b^2)^2=85\\(b-c)^2+(b^2-c^2)^2=75\)

Find \(\displaystyle (a-c)^2+(a^2-c^2)^2\).

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,601

\(\displaystyle (a+b)(b+c)=-1\\(a-b)^2+(a^2-b^2)^2=85\\(b-c)^2+(b^2-c^2)^2=75\)

Find \(\displaystyle (a-c)^2+(a^2-c^2)^2\).

- Moderator
- #2

- Feb 7, 2012

- 2,684

This took me much longer than it should have done!

\(\displaystyle (a+b)(b+c)=-1\\(a-b)^2+(a^2-b^2)^2=85\\(b-c)^2+(b^2-c^2)^2=75\)

Find \(\displaystyle (a-c)^2+(a^2-c^2)^2\).

- Thread starter
- Admin
- #3

- Aug 30, 2012

- 1,121

Brilliant!This took me much longer than it should have done!

-Dan